2022
DOI: 10.1017/s0025315422000522
|View full text |Cite
|
Sign up to set email alerts
|

Using off-the-shelf GPS loggers to assess co-occurrence between marine mammals and small-scale fisheries: a pilot study from the Mediterranean Sea

Abstract: Fisheries constitute a major threat to marine mammals globally. To evaluate the impact of small-scale fisheries (SSF) on regional under-studied marine mammal populations, we tested a novel and cost-effective approach at three data-limited locations of the central and eastern Mediterranean Sea. Using off-the-shelf GPS loggers to track SSF activities and systematic surveys to map the distribution of marine mammals, we assessed the probability of co-occurrence between SSF and marine mammals by reporting areas of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 81 publications
(114 reference statements)
0
3
0
Order By: Relevance
“…Land-and boat-based surveys in Montenegro in 2016-2019 suggested that distribution hotspots for bottlenose dolphins were located within ~16 km from the coast, while a similar study conducted in Albania in 2018-2019 indicated a higher occurrence within ~6 km from the coast; in both areas dolphins were reported to prefer waters shallower than 200 m (Glarou et al, 2022).…”
Section: Distribution and Habitat Preferencesmentioning
confidence: 93%
See 2 more Smart Citations
“…Land-and boat-based surveys in Montenegro in 2016-2019 suggested that distribution hotspots for bottlenose dolphins were located within ~16 km from the coast, while a similar study conducted in Albania in 2018-2019 indicated a higher occurrence within ~6 km from the coast; in both areas dolphins were reported to prefer waters shallower than 200 m (Glarou et al, 2022).…”
Section: Distribution and Habitat Preferencesmentioning
confidence: 93%
“…While the distribution of bottlenose dolphins in the Adriatic Sea frequently overlaps with small-scale fisheries deploying gill and trammel nets (e.g. in the northern Adriatic; Genov et al, 2008, and in southern Montenegro and northern Albania; Glarou et al, 2022), information on these interactions is rarely based on direct observations.…”
Section: Diet and Interactions With Fishing Gearmentioning
confidence: 99%
See 1 more Smart Citation